Development of a Formative Assessment Model for the Pancasila Student Profile Strengthening Project for the Independent Curriculum - Ranti Ermina Sari; Ambiyar; Muhammad Giatman; Muhammad Adri (Postgraduate, University of Mataram, 2025)
This study aims to develop a valid, practical and effective formative assessment Project models for Strengthening Pancasila Student Profiles for use at SMK Negeri 4 Payakumbuh. This model was developed using the Borg and Gall method which refers to the development of Puslitjaknov which consists of the stages of analysis, development, validation, testing and implementation. The results of the study are in the form of the Formative Assessment Model consisting of Diagnostic Activity Syntax, Preparation Activities, Implementation Activities, Monitoring Activities, Assessment Activities, and Evaluation Activities. The Formative Assessment Model has been tested using a model book with a Validity value of 0.89, a model guidebook with a validity value of 0.91 and declared Valid. The practicality of the model obtained a value of 96.65% with a very practical category. The effectiveness of using the H-Gain Score test in the Experimental Class was 0.723 or 72.32 with the Effective category. This finding can be interpreted that the Formative Assessment Model is effective for measuring the development of the Pancasila Student Profile character.